Mycotoxin Dietary Exposure Assessment through Fruit Juices Consumption in Children and Adult Population - Pallarés, Noelia (Toxins (Basel), 2019)
Consumption of fruit juice is becoming trendy for consumers seeking freshness and high vitamin and low caloric intake. Mycotoxigenic moulds may infect fruits during crop growth, harvest, and storage leading to mycotoxin production. Many mycotoxins are resistant to food processing, which make their presence in the final juice product very likely expected. In this way, the presence of 30 mycotoxins including aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin G1 (AFG1), aflatoxin G2 (AFG2), alternariol (AOH), alternariol monomethyl ether (AME), Ochratoxin A (OTA), fumonisin B1 (FB1), fumonisin B2 (FB2), enniatin A (ENNA), enniatin A1 (ENNA1), enniatin B (ENNB), enniatin B1 (ENNB1), beauvericin (BEA), sterigmatocystin (STG), zearalenone (ZEA), α-zearalanol (α-ZAL), β-zearalanol (β-ZAL), α-zearalenol (α-ZOL), β-zearalenol (β-ZOL), deoxynivalenol (DON), 3-acetyl-deoxynivalenol (3-ADON), 15-acetyl-deoxynivalenol (15-ADON), diacetoxyscirpenol (DAS), nivalenol (NIV), fusarenon-X (FUS-X), neosolaniol (NEO), patulin (PAT), T-2 toxin and HT-2 toxin was evaluated in 80 juice samples collected from Valencia retail Market. An efficient Dispersive Liquid-Liquid Microextraction method (DLLME) was carried out before their trace level determination by chromatographic techniques coupled to tandem mass spectrometry. The results obtained revealed the presence of nine mycotoxins namely AOH, AME, PAT, OTA, AFB1, AFB2, AFG2, β-ZAL, and HT2 in the analyzed samples, with incidences ranging from 3 to 29% and mean contents between 0.14 and 59.52 µg/L. Considerable percentages of TDIs were reached by children when 200 mL was considered as daily fruit juice intake.